Prepartum plane of energy intake affects serum biomarkers for inflammation and liver function during the periparturient period - N.A. Janovick; E. Trevisi; G. Bertoni; H.M. Dann; J.K. Drackley (Journal of Dairy Science, 2023)
ABSTRACT: Serum collected from multiparous Holsteins (n = 73) in a previous experiment was used to determine the effect of prepartum plane of energy intake on metabolites related to inflammation and liver function in periparturient cows. Prepartum diets were in a 3 × 2 factorial arrangement over the far-off (d −65 to −26 before expected parturition) and close-up (d −25 relative to parturition until parturition) dry periods. During the far-off period, 2 diets were fed for ad libitum intake (ADLIB) to supply either 100% (100E) or 150% (150E) of National Research Council recommendations for net energy for lactation for mature cows in late gestation. For the third dietary far-off treatment, the 150E diet was fed at restricted intake (REST) to supply 80% (80E) of recommendations. During the close-up period, cows were fed a diet either at ADLIB or REST to supply 150% of net energy for lactation or 80% of net energy for lactation requirements, respectively. Beginning at parturition, all cows were fed a lactation diet through 56 d in milk. Cows fed 150E tended to accumulate more liver lipid postpartum; peak lipid accumulation occurred in all groups on d 14 postpartum. Cows fed 150E tended to have lower serum Ca on d 1 after calving, and cows fed REST had higher Ca than those fed ADLIB. Cows fed 150E tended to have higher serum bilirubin prepartum compared with other groups. Feeding REST in the close-up period resulted in higher bilirubin prepartum compared with ADLIB; bilirubin was positively associated (r = 0.34) with lipid accumulation postpartum. Feeding REST resulted in lower serum vitamin A (an indirect measure of retinol binding protein) prepartum compared with ADLIB, especially when coupled with 80E. Postpartum paraoxonase was negatively associated (r = −0.27) and ceruloplasmin was positively associated (r = 0.21) with liver lipid accumulation postpartum. A larger spike in haptoglobin was observed on d 1 and 7 postpartum for cows fed 100E and 150E during the far-off period followed by REST during the close-up period. The ratio of albumin to globulin in serum was higher for cows fed 100E than for those fed 150E both prepartum and postpartum. Liver activity index indicated poorer liver function for cows fed 150E in the far-off period regardless of close-up diet. Negative liver function was also noted for cows fed 80E and REST. Cows in the 100E group fed ADLIB or REST had positive liver activity index postpartum. Avoidance of gross overconsumption of energy prepartum, particularly during the far-off period, appears best to reduce systemic inflammatory signals and improve liver function.